Congenital myasthenic syndromes in childhood: diagnostic and management challenges. - Kinali, M; Beeson, D; Pitt, M; Jungbluth, H; Simonds, A; Aloysius, A; Cockerill, H; Davis, T; Palace, J; Manzur, A; Jimenez-Mallebrera, C; Sewry, C; et al. (2008)
The Congenital Myasthenic Syndromes (CMS), a group of heterogeneous genetic disorders of neuromuscular transmission, are often misdiagnosed as congenital muscular dystrophy (CMD) or myopathies and present particular management problems. We present our experience of 46 children with CMS, referred to us between 1992-2007 with provisional diagnoses of congenital myopathy (22/46), CMS or limb-girdle myasthenia (9/46), central hypotonia or neurometabolic disease (5/46), myasthenia gravis (4/46), limb-girdle or congenital muscular dystrophy (4/46) and SMA (2/46). Diagnosis was often considerably delayed (up to 18y4 m), despite the early symptoms in most cases. Diagnostic clues in the neonates were feeding difficulties (29/46), hypotonia with or without limb weakness (21/46), ptosis (19/46), respiratory insufficiency (12/46), contractures (4/46) and stridor (6/46). Twenty-five children had delayed motor milestones. Fatigability developed in 43 and a variable degree of ptosis was eventually present in 40. Over the period of the study, the mainstay of EMG diagnosis evolved from repetitive nerve stimulation to stimulation single fibre EMG. The patients were studied by several different operators. 66 EMGs were performed in 40 children, 29 showed a neuromuscular junction abnormality, 7 were myopathic, 2 had possible neurogenic changes and 28 were normal or inconclusive. A repetitive CMAP was detected in only one of seven children with a COLQ mutation and neither of the two children with Slow Channel Syndrome mutations. Mutations have been identified so far in 32/46 children: 10 RAPSN, 7 COLQ, 6 CHRNE, 7 DOK7, 1 CHRNA1 and 1 CHAT. 24 of 25 muscle biopsies showed myopathic changes with fibre size variation; 14 had type-1 fibre predominance. Three cases showed small type-1 fibres resembling fibre type disproportion, and four showed core-like lesions. No specific myopathic features were associated with any of the genes. Twenty children responded to Pyridostigmine treatment alone, 11 to Pyridostigmine with either 3, 4 DAP or Ephedrine and five to Ephedrine alone. Twenty one children required acute or chronic respiratory support, with tracheostomy in 4 and nocturnal or emergency non-invasive ventilation in 9. Eight children had gastrostomy. Another 11 were underweight for height indicative of failure to thrive and required dietetic input. A high index of clinical suspicion, repeat EMG by an experienced electromyographer and, if necessary, a therapeutic trial of Pyridostigmine facilitates the diagnosis of CMS with subsequent molecular genetic confirmation. This guides rational therapy and multidisciplinary management, which may be crucial for survival, particularly in pedigrees where previous deaths have occurred in infancy.